2018
DOI: 10.1080/1745039x.2018.1492805
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soybean oil availabilities on rumen biohydrogenation and duodenal flow of fatty acids in beef cattle fed a diet with crude glycerine

Abstract: Soybean oil with different ruminal availability (whole soybeans (WS), soybean oil (SO) and calcium salts (CS)) was used to evaluate the fatty acid (FA) intake, rumen biohydrogenation (BH) and duodenal flow of FA in Nellore steers fed diets with crude glycerine (CG). Eight castrated Nellore steers were fitted with a ruminal and duodenal silicone cannula, and distributed in a double, simultaneous, Latin square 4 × 4 design with four diets and four experimental periods. Concentrates contained ground maize, urea, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…This change may be caused by a decrease in total VFA, leading to changes in the ruminal digesta bacterial community. Lipid supplementation altered the concentration of all quantified VFA in the rumen, which was triggered by a larger intake of total fatty acid ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…This change may be caused by a decrease in total VFA, leading to changes in the ruminal digesta bacterial community. Lipid supplementation altered the concentration of all quantified VFA in the rumen, which was triggered by a larger intake of total fatty acid ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, when beef cattle are supplemented with lipids, ruminal fermentation can be altered due to the toxicity of long-chain fatty acids, especially unsaturated fatty acids (UFA), to ruminal fibrolytic bacteria and methanogenic archaea (HENDERSON, 1973;JENKINS, 1993), resulting in lower fiber digestibility and DM intake, depending on the composition of basal diet. Thus, different nutritional strategies as whole soybean grain have been used to reduce the UFA effects on rumen microbes or ruminal fermentation parameters in beef cattle (GOMEZ-INSUASTI et al, 2014;GOMEZ-INSUASTI et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Consuming high quantities of SFA, such as C14:0, C16:0, and C20:0, can increase the risk of developing type 2 diabetes and cardiovascular disease. Therefore, they should be moderately ingested [30][31][32]. We found that C14:0 levels were higher in YB loins, whereas C16:0 and C20:0 levels were higher in YW loins.…”
Section: A C C E P T E Dmentioning
confidence: 61%